Exploring the impact of code-switching on English writing and speaking competencies: the case of Grade 12 learners'classroom at Hinkhensile High School - Mokgalaka, Trust (My University, 2024)
Because of an insufficient level of English competence, English is rarely used in most rural South African schools. English exposure is restricted, and many learners are only exposed to the language in classroom. Because of that, most rural high school teachers adopt code-switching in their EFAL classrooms. Therefore, the purpose of this mixed-method study was to explore the impact of code-switching on English speaking and writing competencies of Grade 12 pupils at Hinkhensile High School. Furthermore, the goal of this study was to find out how often code-switching is used by Grade 12 learners and how it impacts their English language speaking and writing competencies. Again, the exploration focused on learners' and teachers' perspectives of code-switching in terms of writing and speaking competencies. In this study, the researcher employed a mixed-method approach, which is a mixture of both quantitative and qualitative research methods; this strategy enabled the researcher to collect and analyse data. Using classroom observation, semi-structured interviews and questionnaires, data were collected from a selected sample of 12th grade pupils and their two EFAL teachers. The study's findings indicated that pupils in the 12th grade at Hinkhensile High School are inadequate in speaking and writing English owing to a lack of English exposure. However, it was shown that code-switching in an EFAL class makes learning more palatable for pupils by boosting their comprehension of the information being taught and also helping them expand their English language vocabulary. Moreover, classroom observations, interviews and questionnaire revealed that code-switching is more common in Hinkhensile High School. In addition, both teachers and learners perceive code-switching as a meaningful tool that helps learners understand the lesson better, as their English language proficiency is low. Most notably, the study found that code-switching improves pupil's English speaking and writing skills by allowing them to employ words or concepts that were better articulated through code-switching in their English writing and speaking interactions.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2024
Keywords: Code-switching; English teachers; English first additional language; Competency; English Second Language; Rural high schools; English language; Code switching (Linguistics); English language -- Writing; English language -- Study and teaching